Study of the Effects of Hardfacing Modes Carried out by FCAW-S with Exothermic Addition of MnO2-Al on Non-Metallic Inclusions, Grain Size, Microstructure and Mechanical Properties - Bohdan Trembach; Illia Trembach; Aleksandr Grin; Nataliia Makarenko; Olha Babych; Sergey Knyazev; Yuliia Musairova; Michal Krbata; Oleksii Balenko; Oleh Vorobiov; Anatoliy Panchenko (Eng, 2025)
This paper investigates self-shielded flux-cored wires with an exothermic MnO2-Al addition and the effect of hardfacing modes on the deposited alloy of the Fe-C-Mn system for the first time. Additionally, the paper proposes a new experimental research methodology using an orthogonal experimental design with nine experiments and three levels. At the first stage, it is proposed to use the Taguchi plan (L9) method to find the most significant variables. At the second stage, for the development of a mathematical model and optimization, a factorial design is recommended. The studied parameters of the hardfacing mode were travel speed (TS), set voltage on the power source (Uset), contact tip to work distance (CTWD), and wire feed speed (WFS). The following parameters were studied: welding thermal cycle parameters, microstructure, grain size, non-metallic inclusions, and mechanical properties. The results of the analysis showed that the listed parameters of the hardfacing modes have a different effect on the characteristics of the hardfacing process with self-shielded flux-cored wires with an exothermic addition in the filler. It was determined that for flux-cored wires with an exothermic addition, the size of the deposited metal grain size is most affected by the contact tip to work distance (CTWD). The research results showed that the travel speed (TS) had the main influence on the thermal cycle parameters (heat input, cooling time) and hardness. The analysis of the deposited metal samples showed that an increase in the travel speed had a negative impact on the number of non-metallic inclusions (NMIs) in the deposited metal. While the size of NMIs was influenced by the wire feed speed and the set voltage on the power source.